2007
DOI: 10.1021/jp076738l
|View full text |Cite
|
Sign up to set email alerts
|

Photodecarbonylation of α-Diketones:  A Mechanistic Study of Reactions Leading to Acenes

Abstract: Poly(acene)s are significant compounds for various electronic applications. A clean, one-step synthesis involves alpha-diketones (2-4), which undergo facile Strating-Zwanenburg photodecarbonylation producing the corresponding poly(acene)s (i.e., anthracene, hexacene, and heptacene, respectively). Compounds 2-4 show weak fluorescence (lambdaF=approximately 525-530 nm and PhiF=approximately 0.1-0.4%) and phosphorescence (lambdaPh=approximately 565-570 nm) and have a small singlet-triplet energy gap (S1-T1 gap, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 28 publications
2
43
0
1
Order By: Relevance
“…91-94 In a clever use of diketone photochemistry, Liao et al designed and synthesized three unsaturated cyclic α-diketones ( 11a-11c , Figure 4), and studied their CO release properties upon visible light irradiation. 48 The results showed that all three compounds ( 11a-11c ) could release CO in organic solvents upon irradiation at 470 nm, and CO release was finished in 10 min.…”
Section: Existing Co-delivery Methodsmentioning
confidence: 99%
“…91-94 In a clever use of diketone photochemistry, Liao et al designed and synthesized three unsaturated cyclic α-diketones ( 11a-11c , Figure 4), and studied their CO release properties upon visible light irradiation. 48 The results showed that all three compounds ( 11a-11c ) could release CO in organic solvents upon irradiation at 470 nm, and CO release was finished in 10 min.…”
Section: Existing Co-delivery Methodsmentioning
confidence: 99%
“…[22] The regularity of spectroscopic data that we observe for nonacene and its radical ions is in support of the theoretical data. The additional strong absorption at 418 nm (377 nm for octacene) is of too short wavelength to be due to the triplet state [26] and may indeed be associated with the electronic structure of the AFM ground state. There is theoretical support for the emergence of an additional strong feature to the red of the b band for heptacene.…”
Section: Methodsmentioning
confidence: 99%
“…3). The study on photogenerated unsubstituted octacene and nonacene by T€ onshoff et al showed strong absorption at 377 nm for octacene and 418 nm for nonacene, which are too short to be due to the triplet state 27,45 and may be associated with an AFM singlet ground state. 46 Driven by the calculation results at the UB3LYP/6-311 +G**//B3LYP/6-31G* level of theory that arylthio substituents placed on terminal rings of the nonacene skeleton will eliminate the total spin, Kaur et al reported two substituted nonacene derivatives (4a, 4b, Fig.…”
Section: Higher Order Acenesmentioning
confidence: 99%